Microbial hazard analysis of cantonese noodle processing - Mangalindan, Shalom Joy L.; Dumelod, Benelyn Domingo (2003.)
ABSTRACT There is a continuing demand for safe and wholesome food. HACCP was developed to address this growing concern for food safety by incorporating control measures to the entire production procedure. The objective of this study is to conduct a microbial hazard analysis, which is the first principle of the HACCP System, for the production of Canton noodles of a certain noodles processing plant in Metro Manila. The study is divided into three phases. Phase I dealt with the formulation of a process flow diagram and the evaluation of the manufacturing practices of the said facility. The steps in producing Canton noodles are: weighing ingredients, mixing dry ingredients (salt, colorant and phosphate) with tap water to form an alkali solution, mixing alkali solution with flour to form a dough, sheeting of dough, slitting, blanching, washing, frying, cooling, and packing. In Phase 2, the microbial load of the raw materials and finished product were evaluated. Both the flour and finished product have very high microbial load reaching 10^8 cfu/g in total aerobic count and Staphylococcus aureus and coliform count of 10^5 cfu/g and. In Phase 3, the possible entry points of the identified microbial hazards were examined. Frying proved enough to kill all the viable microorganisms in the process. However, the cooling and packing procedures recontaminate the noodles by directly exposing the products to the air and personnel, considering that the air and the surface of the personnel's hands are loaded with microorganisms. The resultant final product has high microbial load due to this recontamination.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Noodles -- Microbiology; Food industry and trade -- Philippines -- Safety measures